2014
DOI: 10.5194/bg-11-7009-2014
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in the stratified water column of the Landsort Deep (Baltic Sea)

Abstract: Abstract. The water column of the Landsort Deep, central Baltic Sea, is stratified into an oxic, suboxic, and anoxic zone. This stratification controls the distributions of individual microbial communities and biogeochemical processes. In summer 2011, particulate organic matter was filtered from these zones using an in situ pump. Lipid biomarkers were extracted from the filters to establish water-column profiles of individual hydrocarbons, alcohols, phospholipid fatty acids, and bacteriohopanepolyols (BHPs). A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 113 publications
(128 reference statements)
0
10
1
Order By: Relevance
“…It is noteworthy that previous water column studies in OMZs have reported a significantly lower BHP structural diversity (Berndmeyer et al., 2014; Blumenberg et al., 2007; Kharbush et al., 2013; Sáenz et al., 2011; Wakeham et al., 2007) than observed in this study. We attribute this increase in the number of identified structures to the higher sensitivity and resolving power of the Orbitrap system used for analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…It is noteworthy that previous water column studies in OMZs have reported a significantly lower BHP structural diversity (Berndmeyer et al., 2014; Blumenberg et al., 2007; Kharbush et al., 2013; Sáenz et al., 2011; Wakeham et al., 2007) than observed in this study. We attribute this increase in the number of identified structures to the higher sensitivity and resolving power of the Orbitrap system used for analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…At 1-μ M S ÀII almost all HgS (S) dissolves and forms HgS 2 H À (aq) and Hg (SH) 2 0 (aq) . POM concentrations are lower in anoxic water than in normoxic water in the Baltic Sea (Berndmeyer et al, 2014;Nausch et al, 2008), which further contributes to a high dissolved Hg II fraction and slow settling to sediments. This process prolongs the lifetime of Hg II in the anoxic water column and increases the Hg II reservoir readily available for methylation.…”
Section: A Conceptual Model Of Hg Dynamics Across the Redoxclinementioning
confidence: 99%
“…1a) is ubiquitous in the environment (Bisseret and Rohmer, 1989;Talbot et al, 2003;Talbot and Farrimond, 2007) and has been shown to be produced by a diverse array of bacteria (Rohmer et al, 1984;Talbot et al, 2007a;Talbot and Farrimond, 2007 and references therein). Marine suspended particulate matter (SPM) from anoxic and low-oxygen water columns and marine sediments have also been found to contain a late-eluting BHT isomer (Berndmeyer et al, 2014(Berndmeyer et al, , 2013Blumenberg et al, 2010;Kharbush et al, 2013;Kusch et al, 2018;Rush et al, 2014;Sáenz et al, 2011;Wakeham et al, 2012). The fractional abundance of late-eluting 'marine BHT isomer' was proposed as a way to assess anoxia levels in marine environments, as the ratio of BHT isomer to BHT was found to correlate with anoxia in multiple marine environments (Sáenz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%